Community Empowerment via Online English Education: The Case of 1Jam1000Mimpi - Pawestri, Setyaning; Trisnayanti, Sri (Universitas Mataram, 2025)
The purpose of this community service program is to improve English proficiency among Indonesians through the online community empowerment platform 1Jam1000Mimpi (SJSM). Established by LPDP alumni and awardees in June 2020, the program was created in response to Indonesia’s low English proficiency index, which remains in the low proficiency category. The implementation was carried out online through several stages: (1) recruiting participants via administrative selection, placement tests, and interviews; (2) recruiting volunteers as tutors and organizing committee members; (3) class placement based on proficiency levels (Basic, Intermediate, Advanced) and program types (General English, Conversation, and Exam Preparation); (4) conducting a 12‑week learning program using lectures, discussions, case-based learning, and practice sessions; and (5) final evaluation through participant feedback collected via Google Forms. The results show that within three years, up to mid‑2023, SJSM successfully organized six batches involving more than 1,500 participants and 450 volunteer tutors from across Indonesia. The program has provided inclusive access to English learning, enhanced participants’ motivation, and strengthened networks of educational volunteers.